Development of e-Booklets making nata de pina as a learning resource for Biology Technology Innovation material in the Merdeka Phase E curriculum in high school - Hanifatul Umami; Enni Suwarsi Rahayu (Jurnal Penelitian Pendidikan IPA, 2024)
Research Development of e-Booklet Making Nata De Pina Research-Based Research as a Learning Source of Biological Technology Innovation Material in the Merdeka Phase E Curriculum in High School aims to analyze the influence of the concentration of sprouts extract on the quality of thickness and weight of nata de pina, as well as analyzing the validity, feasibility, and readability of E-Booklet Making Nata De Pina Developed. The development research design uses the Addie model, which consists of 5 stages, namely analysis, design, development, implementation and evaluation. In this study the implementation stage was not implemented. The results of this study were the provision of sprouts in the process of making nata de pina had a significant effect on the thickness of thickness and weight of nata de pina. The best results of the five treatments for the concentration of sprouts extract tested are trial in the K4 treatment with a concentration of sprouts of 100 ml for 500ml of media. The e-Booklet of making Nata de Pina is considered very valid with the acquisition of material validation scores of 90.90% and the validation score of media experts of 93.53%. The e-Booklet making Nata de Pina was declared very feasible with the acquisition of the teacher response score of 96.66% and the student response was 89.52%. As well as the results of the e-Booklet readability test making Nata de Pina is considered high with the acquisition of the Rumpang test score of 98.38%.